Elevated serum creatine kinase levels due to osimertinib: A case report and review of the literature. (March 2022) - Sugimoto, Hiroshi; Matsumoto, Satoshi; Tsuji, Yukio; Sugimoto, Keisuke
Introduction: Osimertinib is a tyrosine kinase inhibitor that targets the epidermal growth factor receptor. Elevated serum creatine kinase level is an uncommon adverse event associated with osimertinib treatment for lung cancer. Case Report: We report a previously healthy 56-year-old woman who developed elevated serum creatine kinase levels during osimertinib monotherapy for epidermal growth factor receptor mutation-positive lung adenocarcinoma. Management & Outcome: During treatment, she experienced leg cramps and her serum creatine kinase levels increased, peaking at 989 U/l. Further investigation revealed no evidence of cardiotoxicity or myositis; thus, osimertinib-induced myopathy was assumed to be the cause of her elevated serum creatine kinase levels. We successfully managed both lung cancer and osimertinib-induced myopathy using 1-week pauses of osimertinib therapy without dose reduction. Discussion: Short-term suspension of osimertinib without dose reduction may be a reasonable option for osimertinib-induced myopathy.